SHORT-RUN AND LONG-RUN IMPACT OF INFLATION, UNEMPLOYMENT, AND ECONOMIC GROWTH TOWARDS POVERTY IN INDONESIA: ARDL APPROACH - Murjani, Ahmadi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2019)
Â Poverty alleviation has become a vigorous program in the world in recent decades. In line with the efforts applied by the government in various countries to reduce poverty, some evaluations have been practised. The impacts of macroeconomic variables such as inflation, unemployment, and economic growth have been commonly employed to be assessed for their impact on the poverty. Previous studies in Indonesia yielded mix results regarding the impact of such macroeconomic variables on the poverty. Different methods and time reference issue were the suspected causes. This paper aims to overcome such problem by utilising the Autoregressive Distributed Lag (ARDL) equipped with the latest time of observations. This paper finds in the long-run, inflation, unemployment, and economic growth significantly influence the poverty. In the short-run, only inflation and economic growth are noted affecting poverty significantly.Â